Comparison of Freehand Sagittal Trajectories for Inserting Pedicle Screws Between C7 and T5. Issue 7 (August 2018) - Oshina, Masahito; Horii, Chiaki; Hirai, Shima; Matsubayashi, Yoshitaka; Taniguchi, Yuki; Hayashi, Naoto; Tanaka, Sakae; Oshima, Yasushi
Abstract : Study Design: Anatomic study using computed tomographic scans. Objective: The purpose of this paper was to determine the trajectory of pedicle screw insertions, in regard to posterior bony landmarks encountered during standard posterior exposure of the spine between the seventh cervical (C7) and the fifth thoracic (T5) vertebrae, when lateral fluoroscopic and radiographic guidance may be obstructed by the scapula and shoulders. Summary of Background Data: Only a few studies have evaluated the intraoperative sagittal trajectory of pedicle screw insertion. Materials and Methods: We assessed 64 participants of a health screening program using whole-spine computed tomographic scans. On the basis of 5 previously reported methods, we designed 3 freehand trajectories: lamina surface method (angle between the superior vertebral endplate and the surface of the lamina), spinous process method (angle between the superior vertebral endplate and a line connecting the tips of the index spinous process and the one cephalad to it), and facet tilt method (angle between the superior endplate and the superior facet tilt). We calculated each of the angles for the C7–T5 vertebrae and determined the most reliable method using coefficients of variation (CV) and intraobserver and interobserver reliability. Results: The lamina surface method had the smallest CVs for C7 and T1, and the mean angles were larger than 90 degrees (range, 94.7–102.4 degrees). The spinous process method had the smallest CVs between T2 and T5, and the mean angles were <90 degrees (range, 85.0–87.0 degrees). The intraobserver and interobserver reliabilities were good or excellent for both methods. Conclusions: The ideal sagittal trajectories for pedicle screw insertion are nearly orthogonal to the lamina surface or the line connecting the spinous processes, but were different for each of the vertebrae. The lamina surface method was the most reliable for C7 and T1, whereas the spinous process method was most reliable between T2 and T5. Level of Evidence: Level III.